Analisis terhadap Kinerja Usaha Kecil Menengah Melalui Entrepreneurial Orientation Dan Entrepreneurial Management Di Kota Bekasi –Jawa Barat - Gede, Adiputra (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACTThe purpose of this study is to examine the influence of Entrepreneurial Orientation and Entrepreneurial Management on the performance of culinary SMEs in the city of Bekasi, West Java. The variables used are Entrepreneurial Orientation measured through dimensions: Innovative, proactive, risk-taking, autonomy, competitive aggressiveness and entrepreneurial management variables are measured through dimensions: strategic orientation, commitment to opportunity, commitment to resources, control over resources, management structure, awards philosophy and culinary performance. The population in this study is the SMEs in Bekasi. The sample in this research is 70 entrepreneurs.  Using purposive sampling as the sampling technique.The data collection technique  is using questionnaire and for the data analysis technique is using multiple regression method. The results of the analysis conclude that there are a significant effects of Innovative, Proactive, Autonomy, Competitive Aggressiveness, Honorable Philosophy and Growth Orientation to the performance of culinary SMEs while Variables Strategic orientation variables, resource orientation, management structure, and entrepreneurship culture have no significant effect on performance variables. Jointly, all these variables are significant to the performance of SMEs.